2009
DOI: 10.1088/0031-9155/54/7/026
|View full text |Cite
|
Sign up to set email alerts
|

Occupational exposure measurements of static and pulsed gradient magnetic fields in the vicinity of MRI scanners

Abstract: Recent advances in magnetic resonance imaging (MRI) have increased occupational exposure to magnetic fields. In this study, we examined the assessment of occupational exposure to gradient magnetic fields and time-varying magnetic fields generated by motion in non-homogeneous static magnetic fields of MRI scanners. These magnetic field components can be measured simultaneously with an induction coil setup that detects the time rate of change of magnetic flux density (dB/dt). The setup developed was used to meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 21 publications
(8 reference statements)
0
29
1
Order By: Relevance
“…Only one study exists in which the movement of the volunteers' heads was measured in the vicinity of 1 and 3 T MR systems [15]. It has been reported that head movements in the stray field of 3 and 7 T MR magnets (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Only one study exists in which the movement of the volunteers' heads was measured in the vicinity of 1 and 3 T MR systems [15]. It has been reported that head movements in the stray field of 3 and 7 T MR magnets (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Due to variations in the direction of the magnetic field outside of the MRI bore, (Siemens) manufacturer specified magnetic field information was obtained to measure the subject rotations relative to changes in the magnetic field direction(36). VMHD vectors were extracted from recorded 12-lead ECGs using techniques described in the Methods section and then rotated to the MRI reference plane (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A second limitation lies in the assumption that the signal contributions of the true ECG recordings taken inside and outside the MRI bore are equal, allowing for extraction of a pure MHD signal, which will not always be the case. The magnetic field outside the MRI scanner can, experience a variation of up to 7.3%, subject to the specific MRI scanner type utilized (36), so the results reported in Figure 3 may have large associated errors.…”
Section: Discussionmentioning
confidence: 99%
“…The fast switching gradient fields are applied for spatial encoding of the MRI signal and can cause peripheral nerve stimulation and implant heating. They are also responsible for the noise in the MRI scanner room, which can reach levels of 100 dB or more and potentially lead to hearing damages [74,119–121,118,122126,30,31,127,128,16,90,129,37,130133,57,58,134,135,69]. …”
Section: Magnetic Fields In An Mri Suitementioning
confidence: 99%